Vascular Injuries Due to Penetrating Missile Trauma in Anti-Terrorism Ops - Rishi Dhillan; Alok Bhalla; Sushil Kumar Jha; Hakam Singh; Aman Arora (Journal of Trauma and Injury)
Purpose Penetrating vascular trauma though less common poses a challenge to all Surgeons. This study was designed to analyse the profile, management modalities of vascular trauma and the outcomes thereof at a Trauma Care Centre in a Tertiary care setting in hostile environment in India. Methods A prospective review of all patients with arterial and venous injuries being transferred to the Trauma Center at out Tertiary Care Center between June 2015 and May 2018 was done. Demographics, admission data, treatment, and complications were reviewed. Results There were a total of 46 patients with 65 vascular injuries, 39 arterial injuries and 26 venous injuries. The age range was 21 to 47 years. Nineteen patients had both arterial and venous injuries. A total of 42 cases presented within 12 hours of injury and complete arterial transections were found in 33 cases (80.49%). There were three mortalities (6.52%) and three amputations (8.33%). The overall limb salvage rate was 91.67% with popliteal artery being the commonest injured artery. Poor prognosticators for limb salvage were increasing time to present to the trauma centre, hypovolemic shock, multi-organ trauma and associated venous injuries. Conclusions Penetrating missile trauma leading to vascular injuries has not been widely reported. Attempting limb salvage even in cases with delayed presentation should be weighed with the threat to life before revascularisation and should preferably be done at a centre with vascular expertise. A team approach with vascular, orthopaedic, general surgeons, and critical care anaesthesiologists all aboard improve the outcomes manifold. Use of tourniquets and early fasciotomies have been emphasized as is the use of native veins as the bypass conduit. This is probably the largest study on penetrating Vascular trauma in anti-terrorism ops from the Indian subcontinent. It highlights the significance of prompt recognition and availability of vascular expertise in optimally managing cases of vascular trauma.